Synthesis and biological evaluation of novel chiral diazepine derivatives as bombesin receptor subtype-3 (BRS-3) agonists incorporating an antedrug approach. Issue 1 (1st January 2015) - Matsufuji, Tetsuyoshi; Shimada, Kousei; Kobayashi, Shozo; Ichikawa, Masanori; Kawamura, Asuka; Fujimoto, Teppei; Arita, Tsuyoshi; Hara, Takashi; Konishi, Masahiro; Abe-Ohya, Rie; Izumi, Masanori; Sogawa, Yoshitaka; et al.
Graphical abstract: Abstract: Novel compounds based on the lead BRS-3 agonists from our HTS compounds2a and2b have been synthesized with the focus on obtaining peripheral BRS-3 agonists. To identify potent anti-obesity compounds without adverse effects on the central nerve system, a labile carboxylic ester with an antedrug functionality was introduced onto the terminal position. Through the extensive synthetic exploration and the pharmacokinetic studies of oral administration in mice, the phenol ester17c was selected due to the most suitable pharmacological profile. In the evaluation of food intake suppression in B6 mice, 17c showed significant in vivo efficacy and no clear adverse effect on heart rate and blood pressure change in dog iv infusion. Our study paved the way for development of anti-diabetes and obesity drugs with a safer profile.